Crop rotation, irrigation system, and irrigation rate on cotton yield in southwestern Georgia. Issue 1 (29th July 2020) - Sorensen, Ronald B.; Lamb, Marshall C.; Butts, Christopher L.
Abstract: Long‐term yield data would be useful for determining crop rotation, irrigation system selection, and irrigation rate for maximum production and economic sustainability. Research was conducted at the USDA–ARS National Peanut Research Laboratory's Multi‐crop Irrigation Research Farm in Shellman, GA (84°36″ W, 30°44″ N), on a Greenville fine sandy loam (a fine, kaolinitic, thermic Rhodic Kandiudult) soil with 0–2% slope. This long‐term study (2001–2013) compared three irrigation systems, three cotton ( Gossypium hirsutum L.) crop rotations, and various irrigation rates on cotton lint yield and quality factors. Irrigation systems were sprinkler, subsurface drip (SSDI), and shallow subsurface drip (S3DI) irrigation compared with a dryland control. Irrigation rates were 100, 66, 50, 33, and 0% of estimated water use. Crop rotations were (a) cotton–corn ( Zea mays L.)–peanut ( Arachis hypogaea L.), (b) cotton–cotton–peanut; and (c) cotton–peanut–cotton. There was no difference in cotton yield by crop rotation. Sprinkler and S3DI systems had greater lint yield than the SSDI system at the 100% irrigation level when averaged across all years and rotations. Lint yield tended to be lower in high rainfall years without respect to irrigation system. Irrigation increased lint yield by an average 10% when rainfall was less than average. All fiber quality factors were within acceptable ranges without any value discounts across years, rotation, or irrigation system. Irrigation system selection should not be based entirely on long‐term yield information but also on field size, system installation cost, irrigation system controls, and crop management.